Mobilization in severe sepsis: An integrative review. Issue 1 (13th November 2014) - Govindan, Sushant; Iwashyna, Theodore J.; Odden, Andrew; Flanders, Scott A.; Chopra, Vineet
<x xml:space="preserve">Abstract</x> Severe sepsis is a leading cause of long‐term morbidity in the United States. Up to half of severe sepsis is treated in non–intensive care unit (ICU) settings, making it applicable to hospitalist practice. Evidence has demonstrated benefits from physical therapy (PT) in myriad conditions; whether PT may benefit severe sepsis patients either within or outside the ICU is unknown. Therefore, we conducted a review of the literature to understand whether early mobilization improves outcomes in patients with severe sepsis in non‐ICU settings. We summarized the pathophysiology of functional decline in severe sepsis, the efficacy of PT in other patient populations, and the potential rationale for PT interventions in patients with severe sepsis. Multiple databases were searched for keywords including length of stay, mortality, costs, mobilization, and PT. Two authors (S.G. and V.C.) independently determined the eligibility of each study. A secondary review including studies of any infectious pathology with PT interventions or sepsis patients within the ICU was also conducted. Our search did not yield any primary literature regarding the impact of mobilization on severe sepsis outcomes in non‐ICU settings. Only 1 retrospective study showed potential benefit of therapy in sepsis patients in the ICU. Similarly, in non‐ICU settings, only 1 study that included patients with bacterial pneumonia reported outcomes after implementing an intervention consisting of early mobilization. These findings suggest that scant data regarding the efficacy of early mobilization following severe sepsis exist. Because hospitalists often care for this patient population, an opportunity for research in this area exists. Journal of Hospital Medicine 2015;10:54–59. © 2014 Society of Hospital Medicine